Divergence within IFRS adoption: the case of depreciation practices of listed banks in Bangladesh - Mezbah Uddin Ahmed (The Indonesian Accounting Review, 2020)
Comparability is one of the qualitative characteristics of financial statements that are prepared in compliance with the International Financial Reporting Standards (IFRS). The objective of this research is to identify whether this qualitative characteristic can be negated even when entities apply IFRS. In achieving the research objective, the depreciation policies adopted by the listed banks in Bangladesh are identified and compared with each other. This research finds that despite increasing effort by accounting standard setters and pressure groups to achieve IFRS-compliance and harmonization in accounting practices, non-compliance and divergence still exists. This research also finds that the divergence in depreciation practices can be of enough significance to negate comparability. The findings of this research expected to assist the international and national standard setters as well as the regulators in understanding the practical issues in implementing accounting standards and developing clearer IFRS implementation guidelines.